SELF-REFERENCE USED BY RADIO ANNOUNCERS IN BANDUNG : A case study ofself-reference variation used by radio announcers ofnineradio stations in Bandung - Peny Miera Sulistyorini, - (2005)
The present research attempts to describe self-reference used by radio announcers in Bandung. In conducting this research, the writer has two questions as follows: I) What sellreference are used by radio announcers in Bandung? 2) What factors influence radio announcer in using self-reference? This research aim 1) To find out self-reference used by radio announcers in Bandung. 2) To find out factors influence radio announcer in using self-reference. Data were collected from recording live broadcastings and interviews. The conversations were tape recorded and then transcript for further analysis. Interviews were also conducted toobtain accurate information about self-reference used by them. The writer applies descriptive qualitative method. The data material is elaborated descriptively and sought to find out the reason in using self-reference. The findings show that radio announcers used more than one type ofself-references. These variation of self-references appeared in pairs live broadcasting. The variation of self-references are gue, saya, aha* I, aing, urang, kuring, ikke, ana, and their own name. Among other self-references, gue tends to be the dominant self-reference used by radio announcers in Bandung. There are three factors influence radio announcers in using variation of self-references, namely format and segmentation of a radio station, target listeners, and participants in performing pairs live broadcasting. The writer suggests that further research conducted should be more elaborate in analyzing variation of self-reference, for instance by studying variation of self-reference used in Television such as in Sinetron or in a talk show, etc.